A retrospective study of SPECT/CT scans using SUV measurement of the normal lumbar vertebrae with Tc-99m methylene diphosphonate - Ruifeng Wang; Cong Shen; Dong Han; Zhaoguo Zhang; Yuhong Zeng; Hulin Wu; Xiaotong Xu; Tao Qin; Nan Yu; Yongjun Jia; Pengtian Zhang; Taiping He; et al. (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2021)
Objective: The aim of this study was to acquire the SUVs for each segment of the vertebral body to explore the rationale for the large variability of the SUVs in normal vertebrae.  Methods: This retrospective study was performed using the images and data from 39 cancer patients who underwent bone SPECT/CT scans with Tc-99m MDP. The SUVmax and SUVmean of the anterior, middle, posterior; left, middle, right; top, middle, and lower of the lumbar vertebrae 1~5, were calculated. The continuous variables were represented by the median values (Q1,Q3), and the differences among various segments were analyzed by Friedman's nonparametric test. The pairwise comparison between groups was corrected by the Bonferroni method. The P<0.05 was considered statistically significant. Results: In this study, 39 patients (31 women and 8 men; mean age, 54.79±9.12 years; age range, 39-71 years) were elucidated. The SUVmax of the L1 and L3 vertebral bodies' parts were significantly different from those of the other portions of the same lumbar vertebra. The SUVmax of the lower posterior portion of the L1 vertebral body was significantly different from that of the upper posterior portion. There were significant differences in the SUVmax between the upper and lower portions, middle and lower portions in the middle of the L3 vertebral body. The SUVmean of the lower posterior portion of L1 and L2 vertebral were significantly different from those of the upper posterior portion. There were significant differences in the SUVmean between the upper and lower portions of the middle of the L3 vertebral body. There were significant differences among the SUVmax and SUVmean of the right, and middle of the vertebral body except for the L2 vertebral body. There were significant differences among the SUVmax and SUVmean of the anterior, middle segments of the lumbar vertebrae body, and the SUVmax of the anterior and posterior parts of the L2 vertebral body, and the SUVmean of the middle and posterior parts of the L1 vertebra. The SUVmax of the middle and posterior portions of the L3～L5 vertebral body, and the SUVmean of the L1～L3, and L5 lumbar vertebrae had significant differences. Conclusion: The difference in the bone metabolism of the lumbar vertebral body is caused by the variation in the horizontal direction of the vertebral body. The bone metabolism in the vertical direction of the lumbar vertebrae has more uniformity. As a quantitative imaging measure, the SUVs might require standardization with adequate reference data to minimize the variability in the participants.